An efficient synthesis of a 6″-BODIPY-α-Galactosylceramide probe for monitoring α-Galactosylceramide uptake by cells. (1st December 2019) - Cheng, Janice M.H.; Chee, Stephanie H.; Dölen, Yusuf; Verdoes, Martijn; Timmer, Mattie S.M.; Stocker, Bridget L.
Abstract: Herein, an efficient synthesis of BODIPY-α-Galactosylceramide 3, which can be used to study the cellular uptake of the potent immunostimulatory parent compound α-Galactosylceramide, is reported. Key in our synthetic strategy is the six-step synthesis of the core BODIPY scaffold (64% yield overall) and its quantitative conversion to an N -hydroxysuccinimidyl ester to facilitate conjugation and purification of the target glycolipid. For the preparation of the core of the glycolipid, the solubility of the lipid acceptor proved to be critical. The ability of BODIPY-αGalCer 3 to activate invariant natural killer cells was then demonstrated in vitro . Graphical abstract: Image 1 Highlights: A fluorescent αGalCer derivative, 6″-BODIPY-αGalCer, was efficiently synthesised. BODIPY N -hydroxysuccinimidyl ester facilitated the conjugation, and the purification of the target glycolipid. 6″-BODIPY-αGalCer activates invariant natural killer (iNKT) cells in vitro.